2018
DOI: 10.13057/biodiv/d190106
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Javan Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) in the Cisokan non-conservation forest areas, Cianjur, West Java, Indonesia

Abstract: Shanidah SS, Partasasmita R, Hudoso T. Parikesit, Meganatara EN. 2018. Short Communication: Javan Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) in the Cisokan non-conservation forest areas, Cianjur, West Java, Indonesia. Biodiversitas 19: 37-41. Javan Leopard Cat (Prionailurus bengalensis javanensis Desmarest, 1816) in the Cisokan non-conservation forest areas, Cianjur, West Java, Indonesia. Biodiversitas 19: xx, xxx.There is no accurate data about the number of leopard individuals in Java … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In comparison to Cisokan, Cianjur, West Java, Indonesia, the proportion of rodent species from other mammals is higher (Withaningsih et al 2018;Husodo et al 2019). This is a feature differing Mordovia of many other mammal faunas, where representatives of the other animal orders predominate (Wirdateti et al 2013;Sulistyadi 2016;Medina et al 2018;Shanidah et al 2018). We assume that the geographic latitude of the area inhabited by rodent species may be decisive in this difference.…”
Section: Resultsmentioning
confidence: 92%
“…In comparison to Cisokan, Cianjur, West Java, Indonesia, the proportion of rodent species from other mammals is higher (Withaningsih et al 2018;Husodo et al 2019). This is a feature differing Mordovia of many other mammal faunas, where representatives of the other animal orders predominate (Wirdateti et al 2013;Sulistyadi 2016;Medina et al 2018;Shanidah et al 2018). We assume that the geographic latitude of the area inhabited by rodent species may be decisive in this difference.…”
Section: Resultsmentioning
confidence: 92%
“…In comparison for Cisakan, Cianjur, West Java, Indonesia, the proportion of insectivorous species from other mammals is 7.7% (Withaningsih et al 2018;Husodo et al 2019). This is a distinctive feature of Mordovia from many mammalian faunas, where representatives of the orders carnivores, rodents and bats predominate (Wirdateti et al 2013;Sulistyadi 2016;Medina et al 2018;Shanidah et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This research was specifically conducted in the future Cisokan sub-watershed area. One study successfully revealed the existence of the Javan leopard in both natural and production forests in Rongga Sub-district [18]. Furthermore, research revealed the existence of Javan leopards in natural forests [20].…”
Section: Ecological Functionmentioning
confidence: 99%
“…Figure 6 show some research that has revealed the presence of several animals in the dry land forests of Rongga Sub-district [16][17][18][19][20]. This research was specifically conducted in the future Cisokan sub-watershed area.…”
Section: Ecological Functionmentioning
confidence: 99%